ASSESING THE IMPACT OF 5G NETWORK ON ECONOMIC IN ASIAN COUNTRIES IN THE PERIOD 2012-2022 - Dang, Manh Duc; Minh, Thu Nguyen Thi (International Journal of Application on Economics and Business, 2024)
This thesis evaluates the impact of 5G technology on the economic growth of Asian countries during the period 2012-2022. As the latest advancement in wireless network technology, 5G has promised unprecedented connectivity speeds, lower latency, and the capacity to simultaneously support a vast array of devices. This research focuses on understanding how the deployment of 5G networks has influenced the economic trajectories of countries within Asia. This region has been at the forefront of 5G adoption. The study employs a quantitative analysis method, combining trend comparison analysis and the Difference in Differences (DID) regression model to assess the economic impact of 5G deployment. By examining data from various Asian countries, this thesis seeks to draw correlations between 5G technology implementation and financial performance indicators such as Gross Domestic Product (GDP) growth, inflation rates, and foreign direct investment inflows. Findings from this research indicate that 5G technology has had a significant, positive impact on economic growth in the region. The high-speed, reliable connectivity offered by 5G has facilitated advancements in various sectors, including manufacturing, healthcare, education, and transportation, contributing to overall economic development. The thesis also discusses the policy implications for countries, particularly Vietnam, aspiring to harness the full potential of 5G technology for economic advancement. Recommendations are provided for policymakers to support the growth of 5G infrastructure and to foster an environment conducive to technological innovation. This study contributes to the existing literature by providing empirical evidence on the economic benefits of 5G technology in Asia. It also offers practical insights for countries looking to leverage 5G technology as a catalyst for economic development.